Evaluation and impact of integrated development of small and medium towns programme - Wishwakarma, R. K.; Prakash , Ajay; Panday , H.B. (New Delhi, 1985)
The study has been divided broadly in four parts. The Part One consists of two chapters: 'Introduction' giving the general background and overall profile of integrated development of small and medium towns and the 'Methodology'. Part Two and Three consist of three chapters, each (chapters 3 to 8) dealing with 'Area Profile', 'IDSMT Project Profile' and 'Implementation and Evaluation' both in Sri Ganganagar (Rajasthan) and Trichur (Kerala). Part Four deals with Chapter 9 on 'Project Management: Gains and Constraints' and Chapter 10 'Policy Implications of Evaluation Findings'. Both are based on the evaluation results of the study. I am sure that these evaluation findings would prove to be very useful for the government in taking certain strate gic policy decisions for the development of small and medium towns.
Keywords: Cities and towns-India